Analisis Perbandingan Nilai Peak Ground Acceleration (PGA) Dengan Metode Esteva dan Oliviera (Studi Kasus : Gempa Bumi Bantul 30 Juni 2023) - Utami, Rizky Widya; Pratiwi, Umi; Susanti, Dwi Budi; Handayani, Wuri (Jurnal Stasiun Geofisika Sleman, 2024)
This study aims to calculate and compare the peak ground acceleration (PGA) values using the Esteva and Oliviera methods, analyze the differences in patterns and values on the contour maps produced by both methods and correlate the PGA values with the Modified Mercalli Intensity (MMI) scale. The case study focuses on the earthquake in Bantul on June 30, 2023, with earthquake data obtained from BMKG. The data were processed using the equations of each method to generate PGA contour maps. The results show that the PGA values calculated using the Esteva method range from 5.47 to 6.73 gal, while the Oliviera method produced higher values, ranging from 9.64 to 12.14 gal. The contour maps of both methods exhibit similar distribution patterns but significant value differences. The Oliviera method's contour map shows higher PGA values than the Esteva method. The results from both methods align with the BMKG earthquake intensity map for the June 30, 2023 event, indicating perceived earthquake intensity at levels III-V MMI. This study demonstrates that the Esteva and Oliviera methods can map PGA distribution, albeit with different sensitivities.